Fast track participatory approach to release of elite cassava genotypes for various uses in Nigerias cassava economy - Dixon, A.; Akoroda, M.O.; Okechukwu, R.U.; Ogbe, F.; Ilona, Paul; Sanni, Lateef O.; Ezedinma, C.I.; Lemchi, J.; Ssemakula, G.N.; Yomeni, M.; Okoro, E.; Tarawali, G. (Springer, 2008)
The aim of the Integrated Cassava Project (ICP) of the International Institute of Tropical Agriculture was to pre-emptively manage the cassava mosaic disease (CMD) to avert an imminent and increasing possible threat of the Ugandan strain of the CMD virus of the pathogen from doing damage to the Nigerian cassava economy. The strategy was to engage in activities that would lead to cultivar-substitution by replacing the susceptible varieties on farmers’ fields with superior genotypes that are not only CMD resistant or tolerant but also high yielding with good dry matter content. A fast track participatory selection approach was used in 2 years to release nine new lines in Nigeria. It was intensive and several lessons were learnt. The varieties released after 2 years were TMS 98/0510, TMS 98/0581, TMS 97/2205, TMS 98/0505, TME 419, TMS 92/0326, TMS 96/1632, TMS 98/0002, and TMS 92/0057.